2009
DOI: 10.1007/s12032-009-9226-8
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil induces arterial vasoconstrictions but does not increase angiotensin II levels

Abstract: Because the mechanisms of 5-Fluorouracil (5-FU) cardiotoxicity have not yet been completely identified, prophylactic options are not available. To our knowledge, there are no published data investigating the use of angiotensin converting enzyme (ACE) inhibitors for 5-Fluorouracil-associated cardiotoxicity. In this study, we aimed to evaluate the influence of 5-FU administration on the diameter of the brachial artery and the levels of angiotensin II. The patients were administered bolus 5-FU/leucovorin in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 14 publications
(14 reference statements)
2
35
3
Order By: Relevance
“…The increases in these groups were significantly higher than that in the control group (p = 0.019). Although in our previous study [10] we were able to demonstrate constriction of the brachial artery diameter due to bolus 5-FU administration, in the present study brachial artery diameters did not significantly decreased in either group before and after 5-FU administration; only a very slight insignificant decrease was seen. The increase of UT-2 levels in the bolus and CI groups thus does not appear to be related to brachial artery diameter values; nevertheless, we consider that this slight decrease may indicate a possible relationship between 5-FU-related cardiac toxicity and UT-2 levels.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…The increases in these groups were significantly higher than that in the control group (p = 0.019). Although in our previous study [10] we were able to demonstrate constriction of the brachial artery diameter due to bolus 5-FU administration, in the present study brachial artery diameters did not significantly decreased in either group before and after 5-FU administration; only a very slight insignificant decrease was seen. The increase of UT-2 levels in the bolus and CI groups thus does not appear to be related to brachial artery diameter values; nevertheless, we consider that this slight decrease may indicate a possible relationship between 5-FU-related cardiac toxicity and UT-2 levels.…”
Section: Discussioncontrasting
confidence: 89%
“…It is possible that, due to measurement technique or other uncertain issues, this vasoconstriction were not clearly identified. In our previous study [10], significant constriction in brachial artery diameters was shown with bolus 5-FU administration. In addition, 5-FU-related vasoconstriction was shown in 2 other studies [8,9].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Eskilsson et al [48] attempted to prevent vasospasm-induced 5-FU cardiotoxicity via preadministration of verapamil without significant clinical effect. Another study by Salepci et al [49] pursued prophylactic administration of ACE inhibitors for the prevention of 5-FU induced cardiomyopathy without effect. Another potentially promising preventive therapy is the pre-administration of a strong antioxidant like probucol, which has demonstrated effectiveness in the lab, but whose efficacy has yet to be confirmed in human subjects [19].…”
Section: Treatment and Prophylaxismentioning
confidence: 99%